Interleukin-6 (IL-6) as a Marker of Endothelial Dysfunction Confirmed Using Flow Mediated Dilatation in Active Smoker - Wicaksono, Arif; Kurnianingsih, Novi; Tjahjono, Cholid Tri; Widito, Sasmojo; Swastikaputri, Valerina Yogibuana; Wihastuti, Titin Andri (Heart Science Journal, 2024)
Background: The pro-inflammatory cytokine interleukin-6 (IL-6) is thought to be the catalyst for endothelial dysfunction caused by smoking. Flow-mediated dilatation (FMD) is a non-invasive method to identify the development of blood vessel endothelial dysfunction at an early stage. However, several studies have not sufficiently explained how smoking and IL-6 interact.Objective: This study focuses on the role of Interleukin-6 (IL-6) in the process of endothelial dysfunction confirmed using non-invasive modalities such as Flow Mediated Dilatation (FMD) in smokers related to the risk of cardiovascular disease in the future with the hope of providing insight in education to smokers to quit smoking.Material and Methods: In this study, we gathered 116 male participants, of which 56 were nonsmokers, and 60 were smokers, and we used IL-6 and FMD testing. SPSS for Windows version 23 will be used to analyze the data.Result: According to the analysis of laboratory tests, the average IL-6 level in light smokers was 67.7±3.2 and in moderate smokers it was 95.1±11.0; with a p-value of 0.009, indicating a significant difference among the groups. The average FMD in the smoking group was 5.4±0.4% (p-value 0.000), whereas the average FMD in the non-smoker samples was 10.9±0.9%. We also looked at the average FMD among light and moderate smokers based on Brinkman Index, which was 5.5±0.4% and 5.0±0.4%, with a p-value of 0.780, indicating no significant difference between the groupsConclusion: Compared to non-smokers, this study demonstrates a correlation between IL-6 and smoking activity. However, there was no statistically significant difference between the prevalence of endothelial dysfunction and the degree of smoking dependence in this investigation.